Environmental Flows to Estuaries and Coastal Lagoons Shape the Salinity Gradient and Generate Suitable Fish Habitat: Predictions From the Coorong, Australia - Brookes, Justin D.; Huang, Peisheng; Zhai, Sherry Y.; Gibbs, Matthew S.; Ye, Qifeng; Aldridge, Kane T.; Busch, Brendan; Hipsey, Matthew R. (Frontiers in Environmental Science, 2022)
Freshwater flows to estuaries shape habitat, transport nutrients to drive productivity, generate a zone over which salinity grades from fresh to marine and provide spawning cues for fish. The aim of this study was to determine how environmental flows export salt from the Murray Darling Basin and assess how freshwater flow arrests seawater ingress which shapes the salinity gradient and determines available habitat for key fish biota in the Coorong. The model platform used to assess the effects of environmental water delivery on salt was the finite volume hydrodynamic model TUFLOW-FV. Coupled to this was a fish habitat suitability model based upon fish salinity tolerance. The Coorong, a large coastal lagoon, and the Murray Mouth lies at the estuary of the Murray Darling Basin in Australia. The North Lagoon is historically estuarine and connected to the Southern Ocean by the Murray Mouth and The South Lagoon is hyper-saline. Salt export from the Murray Darling Basin to the Coorong through the barrages was 496,936 tonnes in 2017-18, 532,333 tonnes 2018-19 and 623,999 tonnes in 2019-20. Without environmental water between 2018 and 2020 there would have been no salt exported from the basin. River flow also arrests salt intrusion from the ocean into the Coorong. Without environmental water, the net import of salt into the Coorong would have been considerably greater, ranging between 1.86 million tonnes in 2018-19 to approximately 2.33 million tonnes in 2019-20. Environmental flows led to fresher conditions in the Coorong and an expansion of suitable fish habitat area. Without environmental water the habitat suitable for mulloway would have contracted by 38% over the three years. A similar trend is evident for black bream, Tamar goby, greenback flounder, yelloweye mullet, congolli and smallmouth hardyhead. The delivery of environmental water plays a key role in exporting salt from the Murray Darling Basin but also arresting the ingress of seawater, which if left unchecked can lead to excessively high salinity in the South Lagoon.